Hardware and software interfacing of the elements of the automated control system - Kolomiitsev, O. V.; Rudakov, I. S.; Kolomiitsev, V. O.; Liubchenko, O. V. (Національний технічний університет "Харківський політехнічний інститут", 2023)
The purpose of the report is to present scientific material on the hardware and software interfacing of the elements of an automated control system. The report presents the results of the study of mathematical and software of the ACS functioning, as well as the purpose and main characteristics of the special purpose data transmission equipment (DTE) AI-011. A universal coupling device (UCD) of the AI-011 SP DTE with a personal computer is proposed. The schematic electrical diagram of the UCD and the block diagram for combining the elements of the ACS are presented. The essence of the UCD operation according to these schemes is revealed. The special software of the ACS is presented, which implements the algorithm for converting codagrams from the format of information exchange in the DTE SP AI-011 in simplex, half-duplex and duplex modes of operation to the format of the RS-232 interface of the serial COM port (USB) of a PC and vice versa.
Keywords: information technology; information transmission system; communication channel; information processing